Genotypic variability in maize for total phenolic, total flavonoids and sugar in response to stalk rot pathogens - NIRUPMA SINGH, MEENA SHEKHAR* RASHMI KIRAN and (Indian Phytopathology, 2016)
This study is planned to determine the total phenolic (TPC), flavonoid (TFA) and Sugar (TSS) in PFSR resistant lines under inoculated and uninoculated conditions against pathogens Fusarium verticilloides and Macrophomina phaseolina. Varied amount of polyphenolic contents observed in inoculated plant. TPC from 199.43 to 88.73: TFA 69.60 to 15.21 and TSS 82.63 to 21.06mg/100g dry weight, whereas in healthy (respective control) plants, this amount observed 160.40: 46.04 and 79.19 respectively. Overall, highest amount of TPC-189.27; TFA-69.60 and TSS-82.63mg/100g dry weights, observed in lines derived from material of NE hills (mixture purple) and from PFSR Yellow pools. Enhanced polyphenolic compounds observed in plants when infected with stalk rot pathogens, which shows that polyphenolic compounds were involved in mechanism of stalk rot tolerance. The outcome of this study reveals that there is genotypic variation in elicitation of enzymes/phenolics in response to infection is directly correlated with the resistance of the plant.